ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KEPUTUSAN PEMBELIAN KONSUMEN PADA YOULANDA BAKERY AND CAKE SHOP DELITUA - Abdianta Peranginangin (Jurnal Niaga & Bisnis (e-journal), 2014)
This study aims to identify and analyze the influence of product, price, location, and service to the consumer purchasing decisions on Youlanda Bakery and Cake Shop Delitua, and more dominant factor influencing it. Author interesting hypothesis that the factor of product, price, location, and service positive and significant impact on consumer purchasing decisions Youlanda Bakery and Cake Shop Delitua, and more dominant factor influencing it is the price factor. The method used is descriptive analysis method and the method of multiple linear regression analysis, using the simultaneous test / simultaneous, partial test, and analysis of the determinants. The data used is primary data and secondary data. This study used a sample of 70 respondents using accidental sampling method. The results showed that the first hypothesis is proven, namely simultaneous / simultaneous factor product, price, location, and service positive and significant impact on consumer purchasing decisions Youlanda Bakery and Cake Shop Delitua. Then, the second hypothesis was also proved, that the price factor is a more dominant factor influencing consumer purchase decisions Youlanda Bakery and Cake Shop Delitua. Keywords: Youlanda Bakery and Cake Shop, products, price, location, service,purchasing decisions